Implementation of Cooperative Learning Model to Improve Students' Learning Outcomes on the Material of Knowing Allah Through Asmaul Husana at SD Negeri 096747 Padang Mainu - Nurhayati, Siti; Suyanti; Ramadhani, Riyo; Manurung, Eliana Saprida; Iziati (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to examine the application of cooperative learning models in an effort to improve student learning outcomes on the material